ANALISIS LQ, dan PROYEKSI KEBIJAKAN PEMINDAHAN IBUKOTA NEGARA KE KALIMANTAN - Yahya Bugis (Pimpinan Cabang Muhammadiyah Kramat Jati, 2023)
This research aims to determine the influence LQ Analized effect of Public Policy KN. Kalimantan Timur Province. This research uses the anized Location Quationt (LQ) to search growth economic in Kalimantan Timur Province. Used data 2017 until 2021